Desenvolvimento de uma ferramenta paramétrica em linguagem APDL para o cálculo da estrutura de um pórtico rolante - Almeida, Rian Felipe Soares de [UNESP] (2015)
This dissertation aims to develop a parametric tool in ANSYS software programming language (APDL language) to calculate the structure of a gantry crane of central beams and reduce the time spent in hours of calculation. This paper first presents the main types of equipment as well as the own gantry cranes, and for this latter describes what are their types and what components make up its structure. Describes about the parameterization in APDL language, about the main solicitations that should be taken into consideration during the dimensioning of the structure, according to the specifications of the standard NBR8400. Present show it was developed the tool, what are their interfaces with the operator and how it works. At the end relates about gaining in saving time when using the program and analyzes the results, of tension and displacement, obtained with the simulation of a generated model